2017
DOI: 10.4102/ojvr.v84i1.1461
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors for <i>Coxiella burnetii</i>, the causative agent of Q fever in the dromedary camel (<i>Camelus dromedarius</i>) population in Algeria

Abstract: Query (Q) fever is a globally distributed zoonotic disease caused by Coxiella burnetii, a bacterial agent for which ruminants are the most prevalent natural reservoir. Data regarding Q fever infection in camels in Algeria are limited. Therefore, a survey to detect seroprevalence of C. burnetii antibodies was conducted among healthy camel populations in a vast area in southeastern Algeria to determine distribution of the Q fever causative organism and to identify risk factors associated with infection. Between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 52 publications
10
26
1
Order By: Relevance
“…Seroprevalence of Q-fever in camels was statistically significant associated with age (p<0.001). This was comparable with the study of [63]. Another studies showed that, like in our study-increasing age increased the seroprevalence of Q-fever in all livestock species [6466] which is not surprising given the cumulative time of potential exposure.…”
Section: Discussionsupporting
confidence: 93%
“…Seroprevalence of Q-fever in camels was statistically significant associated with age (p<0.001). This was comparable with the study of [63]. Another studies showed that, like in our study-increasing age increased the seroprevalence of Q-fever in all livestock species [6466] which is not surprising given the cumulative time of potential exposure.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a study revealed a high seroprevalence of C . burnetii infection in camel populations in south-eastern Algeria, providing strong evidence that Q fever represents a public health and veterinary concern in Algeria [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Saudi Arabia reported a seroprevalence around 50 to 60% of dromedary camels, with the most recent investigation reporting a seroprevalence of 51.5% in 489 camels from Saudi Arabia, whereas the seroprevalence was 34.0% in goats, 30.7% in cattle, and 12.4% in sheep, respectively (372,376,377). A serosurvey performed in Algeria revealed that 71.2% of dromedary camels had circulating C. burnetii Ig (378). A recent study conducted in Kenya confirmed that the highest seroprevalence was in dromedary camels (20%), followed by goats (18%), sheep (13%), and cattle (6%) (379).…”
Section: Camels: Another Animal Reservoir Of C Burnetii Besides Rumimentioning
confidence: 99%